Effects of Birth Weight and Postnatal Nutritional Restriction on Skeletal Muscle Development, Myofiber Maturation, and Metabolic Status of Early-Weaned Piglets - Liang Hu; Xie Peng; Fei Han; Fali Wu; Daiwen Chen; De Wu; Takele Feyera; Keying Zhang; Lianqiang Che (Animals, 2020)
Piglets with light weaning weight commonly have a slow post-weaning growth rate due to impaired skeletal muscle development. Therefore, the present study aimed to investigate the impact of birth weight and nutrient intake on skeletal muscle development, myofiber maturation, and metabolic status of early-weaned piglets. Twelve pairs of normal birth weight and intrauterine growth-retarded (IUGR) piglets (seven days old) were randomly assigned to receive adequate nutrient intake or restricted nutrient intake for 21 days. Serum and muscle samples were collected for further analysis. The results indicated that muscle weight, cross-sectional areas, and muscular glycogen were lower (p < 0.05) in both IUGR and restricted fed piglets. Nutrient restriction decreased the contents of RNA, the RNA to DNA ratio, and the percentages of myosin heavy chain (MyHC) IIx (p < 0.05), whereas increased the activity of β-hydroxy-acyl-CoA-dehydrogenase (HAD), the ratio of HAD to citrate synthase, as well as the percentages of MyHC I (p < 0.05). In addition, nutrient restriction significantly decreased muscular glycogen, mRNA levels of fatty acid transport protein 1, cationic amino acid transporter 1, and glucose transporter 4 in IUGR piglets compared with the other groups (p < 0.05). The results of the present study showed that IUGR impaired skeletal muscle growth and disturbed the hormone and mRNA expression of genes related to energy metabolism, which led to a more severe energy deficit when receiving postnatal nutritional restriction. Postnatal nutritional restriction resulted in delayed myofiber maturation of the piglets, which may be associated with the transformation of MyHC isoform and the change of metabolic status.